PENERAPAN NILAI NILAI FILSAFAT PANCASILA DALAM PEMBENTUKAN KARAKTER PESERTA DIDIK PAKET C KELAS XII DI SKB KOTA BINJAI - Latifah Zahra; Fulka Al Uways Nasution; Anisya; Mita Aulia; Elizon Nainggolan; Michael Yudha Pratama (JURNAL ILMIAH NUSANTARA, 2026)
This study aims to describe the implementation of Pancasila philosophical values in shaping the character of 12th-grade students of the Paket C program at SKB Kota Binjai. The research employed a qualitative descriptive method through observation, interviews, and documentation. The results indicate that Pancasila values have been effectively implemented through habituation, tutor role modeling, collaboration, deliberation, and digital ethics. The value of divinity is practiced through prayer and religious attitudes; humanity is reflected in mutual respect and empathy; unity is shown through cooperation; democracy appears in classroom discussions and deliberation; and social justice is demonstrated through discipline and responsibility. In conclusion, SKB Kota Binjai has successfully internalized Pancasila values, shaping students to be more ethical, responsible, and democratic.